Predictors of purchase satisfaction in e-retailing: Structured literature review - Amado Mateus, Marelby (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Customer satisfaction is a field widely researched in marketing for its influence on the success of companies, but it is also a challenge for e-retailers who must understand and manage the user experience, as well as the changing trends in the buying behavior of their customers. This is why it is important to know what factors influence online shopping satisfaction or e-satisfaction and how to measure it. To achieve this objective, this research develops a structured literature review in which the main scales used in the e-retail sector are identified.